ANALISIS PERAN KECAMATAN CIBINONG SEBAGAI PUSAT PERTUMBUHAN EKONOMI DI KABUPATEN BOGOR - Utami, Isnina Wahyuning Sapta (Jurnal Organisasi dan Manajemen, 2014)
The aims of this study are to identify the development of facilities in Cibinong Subdistric to analyze the role of Cibinong Subdistric as the centre of economic Growth in Bogor regency, and to analyse the changing structure of labour in Cibinong Subdistrict. This research was a quantitative descriptive research. The data used was secondary data which was from Statistic Center Agency (BPS) in Bogor Regency and BAPPEDA. This study using data PODES 2005 and 2011, data from Population Cencus of 2000 and 2010. Quantitative analysis were Scalogram Analysis, transformation labour and descriptif analysis. The result showed that the highest score of facilities was in Cibinong Subdistric. Cibinong Subdistric as the center of economic development growth in Bogor Regency (hierarchy I). Labor structure in Cibinong Subdistrict was changing from dominan in agricultural sector to manufacturing and service sectors. Tujuan dari penelitian ini adalah mengidentifikasi pengembangan fasilitas di Cibinong Kecamatan serta menganalisis peran Cibinong Kecamatan sebagai pusat pertumbuhan ekonomi di Kabupaten Bogor dan struktur perubahan tenaga kerja di Cibinong Kecamatan. Penelitian ini merupakan penelitian deskriptif kuantitatif. Data yang digunakan adalah data sekunder yang berasal dari Badan Pusat Statistik (BPS) di Kabupaten Bogor dan BAPPEDA dengan menggunakan data tahun 2005 dan PODES 2011, data dari Penduduk Sensus 2000 dan 2010. Analisis kuantitatif dalam penelitian ini adalah Scalogram Analisis, tenaga kerja transformasi dan deskriptif analisis. Hasil penelitian menunjukkan bahwa skor tertinggi fasilitas berada di Kecamatan Cibinong. Kecamatan Cibinong sebagai pusat pertumbuhan pembangunan ekonomi di Kabupaten Bogor (hirarki I). Struktur tenaga kerja di Kecamatan Cibinong berubah dari dominan di sektor pertanian dengan sektor manufaktur dan jasa.